2001
DOI: 10.4141/s00-073
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Cu(II) in soil by X-ray absorption spectroscopy

Abstract: Frenkel, A. I. and Korshin, G. V. 2001. Studies of Cu(II) in soil by X-ray absorption spectroscopy. Can. J. Soil Sci. 81: 271-276. Based on original data for copper, this paper evaluates the use and advantages of X-ray absorption fine structure (XAFS) in studies of heavy metals in soils. The structural parameters of the Cu 2+ target were quantified for soil exposed to copper and the same soil eluted with 0.1 M HCl. Experimental data were obtained using synchrotron sources of second and third generations. X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This is in accordance with the results of X-ray absorption analyses by other studies (e.g. Frenkel and Korshin, 2001;Lewis et al, 2011), which showed that both Pb and Cu are bound predominantly by oxygen-containing functional groups in soils, which may be associated both with organic (humic-like) and inorganic metal-oxide (e.g. Pb-and Cu-oxides) or even silicate phases.…”
Section: Iron Fractionation As Related To That Of the Trace Metalssupporting
confidence: 93%
“…This is in accordance with the results of X-ray absorption analyses by other studies (e.g. Frenkel and Korshin, 2001;Lewis et al, 2011), which showed that both Pb and Cu are bound predominantly by oxygen-containing functional groups in soils, which may be associated both with organic (humic-like) and inorganic metal-oxide (e.g. Pb-and Cu-oxides) or even silicate phases.…”
Section: Iron Fractionation As Related To That Of the Trace Metalssupporting
confidence: 93%
“…The EXAFS data analysis of the CuPd/PVPy sample revealed the presence of two Cu–O coordination shells consistent with Cu 2+ ions coordinated with O atoms at short (1.94 Å) and longer (2.52 Å) distances and a Cu–Pd contribution exhibiting a distance and coordination number compatible with the results obtained at the Pd K‐edge . The two different Cu–O distances found were also confirmed by the presence of the two peaks (labelled C and D) between 8981 eV and 8993 eV in the first derivative of the XANES spectrum of the CuPd sample (Figure ) that are normally associated to a tetragonal distortion of the CuO 6 octahedron that gives shorter equatorial and longer axial Cu−O bonds. In the absence of a tetragonal distortion, the splitting observed in Figure disappears.…”
Section: Resultssupporting
confidence: 72%
“…5b) indicates that the axial ligand(s) are located at about 1.9 + 0.4 Å or 2.3 Å (Frenkel et al, 2000). We cannot confirm whether Cu has one or two axial ligands but, in principle, both outcomes are reasonable because Cu in aqueous solution prefers a 5-fold elongated square pyramidal coordination that is likely to be competitive with a 6-fold distorted octahedral coordination (Frenkel and Korshin, 2001;Bryantsev et al, 2008).…”
Section: Shell-by-shell Fits Of Exafs Spectramentioning
confidence: 80%